Biodiesel Production from Castor Oil by Using Calcium Oxide Derived from Mud Clam Shell - Ismail, S.; Ahmed, A. S.; Anr, Reddy; Hamdan, S. (Journal of Renewable Energy, 2016)
The catalytic potential of calcium oxide synthesized from mud clam shell as a heterogeneous catalyst for biodiesel production was studied. The mud clam shell calcium oxide was characterized using particle size analyzer, Fourier transform infrared spectroscopy, scanning electron microscopy, and BET gas sorption analyzer. The catalyst performance of mud clam shell calcium oxide was studied in the transesterification of castor oil as biodiesel. Catalyst characterization and transesterification study results of synthesized catalyst proved the efficiency of the natural derived catalyst for biodiesel production. A highest biodiesel yield of 96.7% was obtained at optimal parameters such as 1 : 14 oil-to-methanol molar ratio, 3% w/w catalyst concentration, 60°C reaction temperature, and 2-hour reaction time. Catalyst reusability test shows that the synthesized calcium oxide from mud clam shell is reusable up to 5 times.